FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS AUDIT (STUDI PADA AUDITOR INSPEKTORAT KABUPATEN KUANTAN SINGINGI) - Dessy Kumala Dewi; Zulkarnain (Fakultas Ekonomi Universitas Pasir Pengaraian, 2021)
Audit quality is an assessment of a process in carrying out the examination process and the final result of an audit process carried out by the auditor. This study aims to analyze what factors affect audit quality. The population in this study is the auditor of the Inspectorate of Kuantan Singingi Regency. The sample used in this study was 10 samples which weredetermined using purposive sampling technique.This type of research is descriptive quantitative. The data of this study were obtained from the questionnaire given to the respondents (sample). The analysis used in this study is multiple regression analysis using SPSS version 21. The results of this study indicate that partially the competence variable has a significant effect on audit quality with a significance value of 0.09 < 0,05. The work experience variable has a significant effect on audit quality with a significant value of 0.043<0.05. Meanwhile, the variable of professional skepticism has no effect on audit quality 0.101>0,05.